A textbook on food contamination and safety - Nanbiar, Vanisha (New Delhi, India : Anmol Publications, 2004)
Targetted towards the health conscious citizens of our country, chiefly the Home Science "Janta", this book attempts to answer queries on food safety and food quality; how and why food is often contaminated/adulterated; and simple tests to detect adulteration from various food items ranging from milk and milk products, oils and fats, spices, fruits and vegetables, sugar and sweets, grains and flours, beverages and meat, fish and poultry.
Foreword -- Preface -- Acknowledgements -- 1. Introduction -- 2. Bacterial Contamination of Foods -- 3. Metal Contaminations -- 4. Harmful Substances that Enter Through Food -- 5. Contaminations in Milk and Milk Products -- 6. Contaminations in Fats and Oils -- 7. Contaminations in Spices and Condiments -- 8. Contaminations in Fruits and Vegetables -- 9. Contaminations in Sugar -- 10. Contaminations in Water and Beverages -- 11. Contaminations in Food Grains and Flours -- 12. Processed Foods and Packaging -- 13. Food Addtives -- 14. Contaminations in Poultry Meat, Fish and Sea Food -- Select Readings.
Includes bibliographical references.
Keywords: FOOD CONTAMINATION -- PREVENTION